EVALUASI PENERAPAN SMK3 BERDASARKAN TINGKAT KEPATUHAN PERSONAL - Sediyanto Sediyanto (KURVATEK, 2018)
The successful implementation of Occupational Safety and Health Management System (SMK3) in the company can not be separated from the concern of workers and managerial parties. This study aims to determine what indicators affect personal compliance, priority indicators affecting personal compliance level and to know evaluation of the performance of SMK3 implementation on the implementation of UKRIDA Education Hospital project development using SPSS method, personal compliance analysis and performance analysis of SMK3. Research data collected by distributing to 28 respondents in PT. PULAUINTAN. Experts are the project managers. The results of the study, personal compliance analysis method resulted in high adherence or 64.58%. Furthermore, the performance analysis of SMK3 implementation, the analysis result shows the performance value of SMK3 is or 59%. Then with the results of high compliance analysis and performance is then there is need for improvement action performance of SMK3 implementation to improve the implementation of SMK3. Keywords: Personal Compliance, SMK3 implementation Performance, SPSS, Personal Compliance Evaluation, Effect of personal compliance on SMK3 performance